IMPLEMENTASI PENDIDIKAN KARAKTER DALAM MEMBENTUK PERILAKU SOSIAL DAN KEAGAMAAN SISWA - Anis Fauzi; Mujibudda’wah Mujibudda’wah (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2016)
This research aims at finding character educationa program and its implementa-tion in building social and religious character at the students of SMPN 1 Cimanuk Kabupaten Pandeglang. It used qualitative descriptive which is used to describe current phenomenon about the implementation of character education in buil-ding social and religious character of at the students of SMPN 1 Cimanuk Kabu-paten Pandeglang. The result of the research shows that (1) charcter education program is a part of students building program; (2) the implementation of charac-ter education such as reciting prayer together, reciting short Surah; (3) students like to interact with other people, help each others, visit sick students, shake hand, do the picket, and cooperate.